2015
DOI: 10.1002/mren.201500042
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge‐Based Production of Waterborne Hybrid Polymer Materials

Abstract: Hybrid waterborne dispersions provide improved performance in established applications and allow targeting new applications that are out of reach of the conventional homogeneous latexes. They are product‐by‐process materials that are produced by either emulsion or miniemulsion polymerization and whose characteristics are determined in the reactor. Therefore, it is crucial to produce them by means of an optimal process strategy. This work reviews the fundamental knowledge available as well as the missing parts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 141 publications
(225 reference statements)
1
27
0
Order By: Relevance
“…In an attempt to pave the way to process optimization and on-line control, this work aims at evaluating the capability of the model to describe the evolution of the particle morphology during seeded semibatch emulsion polymerization, which is the most widely used process for the polymerization of waterborne polymer-polymer hybrids [55]. The evolution of the particle morphology during the copolymerization of styrene (S) and butyl acrylate (BA) on methyl methacrylate (MMA)-BA seeds of different Tgs was determined by Cryo and conventional TEM.…”
Section: Sundberg and Coworkersmentioning
confidence: 99%
“…In an attempt to pave the way to process optimization and on-line control, this work aims at evaluating the capability of the model to describe the evolution of the particle morphology during seeded semibatch emulsion polymerization, which is the most widely used process for the polymerization of waterborne polymer-polymer hybrids [55]. The evolution of the particle morphology during the copolymerization of styrene (S) and butyl acrylate (BA) on methyl methacrylate (MMA)-BA seeds of different Tgs was determined by Cryo and conventional TEM.…”
Section: Sundberg and Coworkersmentioning
confidence: 99%
“…In the production of waterborne binders (for coatings), emulsion polymerization is the most popular process. However, when it comes into hybrid waterborne binders, miniemulsion polymerization emerged as an alternative process, to overcome the limitations of emulsion polymerization when the inorganic material must be incorporated into the polymer particles [48][49][50]. Moreover, equilibrium morphology simulations have demonstrated that if the nanoparticles present good wettability in the monomer phase, they can be encapsulated in monomer nanodroplets and hence hybrid latexes with encapsulated morphology can be produced [51].…”
Section: Synthesis Of Acrylic/ceo 2 Hybrid Nanocomposites By Seeded Smentioning
confidence: 99%
“…Furthermore, the emerging demand of modern society to reduce the emission of volatile organic compounds (VOC) led the interest of the scientific community to develop a new type of coatings: waterborne coatings [15] that use water as a medium to disperse a resin, thus making these coatings ecofriendly and easy to apply. These coatings are environmentally friendly, as American and European regulations require waterborne coatings to have a VOC content of less than 3.5 pounds per gallon of water.…”
Section: Introductionmentioning
confidence: 99%